(untitled) (Training and Practice : Journal of Educational Sciences, 2014)
My essay is dealing with peculiarities of the language used by the youth of today with special emphasis on kindergarten teacher trainees who will use the Hungarian language professionally as the base of their daily work. During this investigation more and more questions have emerged: how and due to what kind of influences is our mother tongue changing today? How does this appear in the youth slang? How do students consider their use of language today and do they intend to modify it after the university years? Do they understand the language they use? Do they feel their responsibility, do they show a model of the pedagogue in their profession regarding their mother tongue? The simplified answer is: yes. Yes, the students feel their responsibilty regarding their mother tongue. This finding is good news after so many different forecasts visioning the death of the language. It is giving us great satisfaction.